A dual supramolecular crosslinked polyurethane with superior mechanical properties and autonomous self-healing ability. (24th April 2020) - Xu, Shaobin; Sheng, Dekun; Zhou, Yan; Wu, Haohao; Xie, Haopu; Tian, Xinxin; Sun, Yinglu; Liu, Xiangdong; Yang, Yuming
Abstract : The dual-dynamic networks endow polyurethane with excellent mechanical properties and autonomous self-healing ability. Abstract : To prepare a robust material with high self-healing capability under ambient conditions is still a great challenge. Herein, a novel self-healing polyurethane is developed via a dual-dynamic network design, in which multiple H-bonding and metal-coordinated bonds (zinc–imidazole interaction) were incorporated into a polyurethane matrix. Benefiting from the dual-dynamic network, the synthesized metallopolymers exhibit excellent mechanical properties, such as high tensile strength (from 6.68 MPa to 14.38 MPa), excellent stretchability (about 2000%) and superior toughness (from 55.61 MJ m −3 to 96.21 MJ m −3 ). Moreover, these metallopolymers show good self-healing capability. After healing under ambient conditions for 48 hours, the tensile strength and strain at break of PU-IZ/Zn-0.50 can reach up to 7.13 MPa and 1800%, respectively. The dual-dynamic crosslinked metallopolymers might provide a novel approach to design tough and self-healable materials for various industrial applications.